Physicochemical Characteristics of Chitosan–Alginate Scaffold Containing Atorvastatin - Hananeh Hamedfar; Tayebeh Zivari-Ghader; Abolfazl Akbarzadeh; Soodabeh Davaran (Advances in Polymer Technology)
In addition to being a lipid-lowering medication, atorvastatin (ATV) is an anti-inflammatory agent. When there is a bone defect or inflammation of adjacent tissues, it aids in bone repair. This study aimed to develop a chitosan–alginate (CS/ALG)–tripolyphosphate (TPP)–ATV hybrid hydrogel as a drug delivery system, using a tissue engineering scaffold for the first time. For this purpose, a CS/ALG hydrogel crosslinked with TPP was developed. The delivery profile of ATV and its physicochemical properties such as particle size and hydrogel swelling percentage were determined. The structure and morphology of the hydrogels were analyzed using Fourier transform infrared spectroscopy and scanning electron microscopy. As a result, an alginate–chitosan hydrogel with a TPP crosslinker was prepared. The results revealed that drug loading was nearly complete, and the first hour revealed a 25% explosive release. The drug was gradually released over 10 hr at approximately 35%. The amount of crosslinker used significantly influenced the encapsulation gain and release profiles. Owing to its high porosity and swelling, the CS/ALG hydrogel crosslinked with PPT is an ideal scaffold for loading drugs, macromolecules, and cells.